치위생학, 간호학 전공 학생의 자원봉사활동 경험에 따른 전공만족도와 직업존중감 조사 - 신미아; 안권숙; Shin, Mi-A; Ahn, Kwon-Suk (Han'guk Ch'iwisaeng Hakhoe chi, 2012)
Objectives : The purpose of this study is to investigate satisfaction in major and job esteem of college students in dental hygiene and nursing department according to volunteering. Methods : This study was used on a descriptive research design. participants of this study were 378 college students in some region from April 30th to May 21th. The collected data were analyzed by SPSS Program(version 20.0) using descriptive statistics. Results : Volunteering experience subjects was 24.3%, the subjects did not experience volunteering was 75.7% and volunteering related to major was 59.8% and it was 40.2% of unrelated volunteering. Volunteering experience by general characteristics was influenced significantly by grade(p= .000), major(p= .000), economic status(p= .007). Volunteering experience by major relevant characteristics of subjects was not influenced significantly. The major satisfaction by volunteering was a little higher on volunteering experience subjects than non-experienced subjects. and was not influenced difference significantly(p= .786). The job esteem by volunteering was higher volunteering experience subjects than non-experienced subjects and was influenced significantly(p=.005). Conclusions : College students majoring in the department of dental hygiene and nursing is somewhat lower the volunteering experience. The major satisfaction and job esteem of college students was influenced by volunteering. therefore, the need to plan ways to increase participation and provide information and opportunities is to invigorate the function of the volunteering service which is also considered as one of the functions of the university.